ANALYSIS OF CONSUMER DECISIONS IN DETERMINING CULINARY CHOICES AT "X" UNIVERSITY - Achmad Tarmizi; Dwi Aprillita (Jurnal Scientia, 2023)
Analyzing consumer food choices is an important topic in business and marketing. Consumer decisions have a significant impact on market demand and profitability. In today's era of technology and information, consumers have extensive access to culinary information. They are becoming more discerning regarding food choices, especially with increasing health and nutrition awareness. Therefore, culinary businesses must understand factors such as taste, price, quality, availability, promotion, and branding influencing consumer decisions. This understanding allows businesses to develop effective strategies to increase sales and consumer satisfaction. This research aims to test and analyze Consumer Decisions Analysis in Choosing Culinary Options at University X. The research method uses purposive sampling to collect primary data from first-semester students taking introductory microeconomics courses. The research population consists of 100 students. This study employs Structural Equation model analysis using SmartPLS. The research findings indicate that the size of the food has a very weak influence on consumer decisions. Consumers do not consider size when deciding what to purchase, as they pay more attention to other factors such as taste, quality, price, or personal preferences. On the other hand, food characteristics significantly impact consumer decisions, as consumers tend to choose food based on quality, taste, availability, and other aspects related to their culinary experience. This reflects a shift in consumer preferences that prioritize quality and variety in their food choices, including considerations related to health and nutrition.